The Implementation of Rectifier Technology For Small Scale Industries Producing Exhaust Pipe in Purbalingga - Eddy Triyono; S Setyowati Rahayu; Vonny SA Budiarti; Bambang Sumiyarso (Logic : Jurnal Rancang Bangun dan Teknologi, 2019)
Purbalingga Regency Government policy to include exhaust pipe as one of the region's leading commodities is considered as one finest step. Various types of motor vehicle are produced and as a result small industry engaged in motor vehicle spare parts are emerging, including exhaust parts. The choice of technology with the metal industry, especially the exhaust in Purbalingga aims to improve the competitiveness of regional superior competency-based industries, namely revitalizing the industrial sector in order to exist and be able to develop, and be able to transfer technology about improving exhaust quality which has an impact on increasing the exhaust industry's income. The exhaust products from SMEs have exclusivity in the tip of exhaust pipe that is coated with metal, thus improve the appearance and quality of the exhaust. But the exhaust product with a variety of metal coated parts turned out to be incompatible with industry standards, which consequently the quality of the results of the dull metal coating process, easy to peel and rusty. For this reason, Semarang State Polytechnic implements rectifier equipment for metal coating. The methods used were the founding of an Institution Forum for the Purbalingga Exhaust Cluster Association, metal coating technique training for workers, operating tests, operational procedures and operational assistance. The results obtained are rectifiers for metal coating with current outputs of 10 A, 20 A, 30 A, 40 A, 50 A.